Psychodynamically Oriented Psychopharmacotherapy: Towards a Necessary Synthesis - Iannitelli, Angela; Parnanzone, Serena; Pizziconi, Giulia; Riccobono, Giulia; Pacitti, Francesca (Frontiers in Human Neuroscience, 2019)
The discovery of psychoanalysis and of psychotropic medications represent two radical events in understanding and treatment of mental suffering. The growth of both disciplines together with the awareness of the impracticality of curing mental suffering only through pharmacological molecules – the collapse of the “Great Illusion” - and the experience of psychoanalysts using psychotropic medications along with depth psychotherapeutic treatment, have led to integrated therapies which are arguably more effective than either modality alone. The authors review studies on the role of pharmacotherapy with psychoanalysis, and the role of the analyst as the prescriber. The psychotic disorders have specifically been considered from this perspective.